Peran Pemerintah dalam Perlindungan Tenaga Kesehatan Terpapar Covid–19 - Rustam Effendi; Handayani Handayani (Universitas Faletehan, 2022)
The number of confirmed cases of Covid-19 in Indonesia was extremely high. The distribution rate as of June 27, 2021, was confirmed 2,093,962, died 56,729 and recovered 1,842,457. The government’s role in the protection of health workers was highly needed. Several policies from the government were contained in the regulatory provisions, such as bonuses payment and death compensation for health workers and Covid-19 vaccine program for medical personnel. The government's efforts to prevent the spread and transmission of Corona virus included the policy of staying home, wearing masks, and washing hands. The purpose of this study was to analyze the stages that have been carried out by the Indonesian government when dealing with Covid-19 and to protect health workers. The study used systemic literature review. From the 7 articles obtained, Indonesia had implemented policies to control and prevent the transmission of Covid-19. The policies required supports, participations and people awareness. Good and organized regulations and health system were needed. Patterned coordination among stakeholders, especially the central government and regional governments, and SOPs for the prevention and control of Covid-19 were required to completely inhibit the spread of Covid-19 infection.